2014
DOI: 10.1159/000365395
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the GM-CSF Signaling Pathway in Macrophage Pro-Repair Activities

Abstract: Objective: Macrophages play a critical role in intestinal wound repair. However, the molecular pathways that regulate macrophage wound repair activities remain poorly understood. The aim of this study was to evaluate the role of GM-CSF receptor signaling in the wound repair activities of macrophages. Methods: Murine macrophages were differentiated from bone marrow cells and human macrophages from monocytes isolated from peripheral blood mononuclear cells of Crohn's disease (CD) patients. In vitro models were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Although GM-CSF is traditionally applied in the treatment of blood system diseases, multiple in vitro studies disclose that GM-CSF may play an essential role in the cascade of the healing process due to its function in the modulation of several key resident cells in wounds, such as fibroblasts, keratinocytes, and macrophages. [32][33][34] Postiglione et al reported the expression of GM-CSF receptor in human fibroblasts. The proliferation activity of fibroblasts was modulated by different concentrations of GM-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Although GM-CSF is traditionally applied in the treatment of blood system diseases, multiple in vitro studies disclose that GM-CSF may play an essential role in the cascade of the healing process due to its function in the modulation of several key resident cells in wounds, such as fibroblasts, keratinocytes, and macrophages. [32][33][34] Postiglione et al reported the expression of GM-CSF receptor in human fibroblasts. The proliferation activity of fibroblasts was modulated by different concentrations of GM-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…A possible hypothesis is that excessive activation of monocytes occurs in response to bacterial translocation across the epithelium and to minor defects in bacterial clearance or in MDP-induced tolerance. Notably, the paradoxical efficacy of GM-CSF in some cases of CD may be due to the correction of such defects in epithelial monocytes, for example by rescuing their epithelial repair function[37]. Another critical function for mucosal monocytes may concern the induction of antimicrobial peptide production by Paneth cells[38]; indeed, a defective production of defensins after bacterial translocation may result in altered shaping of gut microbiota, leading to inflammatory amplification in a vicious circle.…”
Section: Discussionmentioning
confidence: 99%
“…Since their identification, several studies demonstrated that these Th1/Th17 cells, also named pathogenic Th17 cells, are involved in the pathogenesis of inflammatory diseases including autoimmune encephalomyelitis, multiple sclerosis and colitis 30,32 . One of pathogenic Th17 cells product, GM‐CSF, is a key factor known to play an important role in gut homeostasis 33–35 . Indeed, GM‐CSF is secreted by many other cell types such as epithelial cells 36 and is a key factor in sustaining and promoting innate and adaptive mucosal immune responses 37,38 …”
Section: Introductionmentioning
confidence: 99%
“…30,32 One of pathogenic Th17 cells product, GM-CSF, is a key factor known to play an important role in gut homeostasis. [33][34][35] Indeed, GM-CSF is secreted by many other cell types such as epithelial cells 36 and is a key factor in sustaining and promoting innate and adaptive mucosal immune responses. 37,38 The objective of this study was to probe for a role of GM-CSF in the vaccine-induced reduction of H. pylori infection.…”
mentioning
confidence: 99%